La langue au coeur de l’expérience des francophones en santé au Nouveau-Brunswick : étude exploratoire des expériences de la discordance linguistique en santé - Hébert, Shayna-Eve; Violette, Isabelle; Forgues, Éric; Erazo, Atilio; MacLeod, Krystal Kehoe (Minorités linguistiques et société, 2026)
Dans cette étude qualitative exploratoire, nous examinons les expériences de discordance linguistique rapportées par 12 francophones du Nouveau-Brunswick (Canada), province dans laquelle le français est une langue officielle, mais en situation minoritaire. En nous basant sur des entretiens semi-dirigés, nous cherchons à comprendre les expériences de discordance linguistique vécues par la patientèle au sein de cliniques et d’hôpitaux publics faisant partie des réseaux de santé Horizon et Vitalité. L’analyse de contenu thématique (Paillé et Mucchielli, 2021) des récits des patients et des patientes révèle trois types de discordance linguistique auxquels sont liés de multiples effets et émotions chez les participantes et les participants ainsi que des préoccupations à l’égard des droits linguistiques de la minorité francophone. Nous proposons, pour conclure, des pistes pour poursuivre les recherches dans le domaine de la discordance linguistique et pour faciliter l’accès aux services de santé en français dans cette province. In this exploratory qualitative study, we examine experiences of language discordance reported by 12 Francophones in New Brunswick (Canada), a province in which French is an official language but remains minoritized. Drawing on semi-structured interviews, we seek to understand patients’ experiences of linguistic discordance within public clinics and hospitals of the Horizon and Vitalité health networks. A thematic content analysis (Paillé & Mucchielli, 2021) of participants’ accounts reveals three types of linguistic discordance, associated with a range of effects and emotions among participants, as well as concerns regarding the linguistic rights of the Francophone minority. We conclude by proposing directions for future research on linguistic discordance and for improving access to French-language health services in this province.

Insight into Post-Pandemic Needs in Healthcare and Well-Being Among Francophone Families in the Canadian Prairies - Keough, Catelyn; Turgeon, Marianne; Proulx-Cullen, Elyse; Leis, Anne; De Moissac, Danielle; Marchak, Kristan; Gnidehou, Sedami (International Journal of Environmental Research and Public Health, 2026)
Francophone populations outside Quebec were disproportionately affected by the COVID-19 crisis. Despite French being one of Canada’s official languages, access to information and services in French remains limited. This study examined Francophone families’ (FF) post-pandemic health and well-being needs (PPHW) in the Canadian Prairie provinces. An online survey assessed PPHW needs among 319 FF in Alberta (AB), Saskatchewan (SK), and Manitoba (MB). Respondents ranked PPHW needs from a predefined list; logistic regression analyzed socio-demographic influences. Divided into AB/SK and MB cohorts, sociodemographic profiles were statistically distinct for many variables, but with similarities found in gender of respondents (women: 73% in AB/SK, 79% in MB), marital status (married: 81% in AB/SK, 88% in MB), area of residence (urban: 86% in AB/SK, 81% in MB), and number of children (2 children: 49% in AB/SK, 41% in MB). Three high-priority needs were shared across provinces: (1) access to recreational, athletic, and artistic activities in French for children (variations by child gender); (2) access to French healthcare professionals (variations by education level and language difference); and (3) social activities in French for families. AB/SK respondents prioritized mental health services in French for adults and youth. MB families prioritized belonging to a Francophone community (variations by gender of children) and education services in French (variations by age of children). Understanding these common and province-specific priorities can inform policy and service planning.

Official Language Minority Communities in Ontario: (In)visibility of Nursing Care - Muray, Mwali; Chartrand, Julie; Perron, Amélie (Aporia, 2026)
Despite Canada’s linguistic duality, French-speaking minority populations continue to face significant barriers in accessing equitable health care. Investigating two key research questions, this study explores: (1) What are the lived experiences of registered nurses and nursing students caring for French-speaking patients in Ontario? and (2) How do French-speaking patients navigate the health care system to access care in their preferred language? Using qualitative methodology informed by interpretive phenomenology, 31 participants were interviewed individually between 2018 and 2019, offering firsthand accounts of their experiences. Findings reveal a paradox of (in)visibility: French-speaking patients and nursing providers remain invisible when they adapt to systemic shortcomings but become highly visible when they advocate for equitable care. The study highlights the urgent need for the effective and consistent implementation of the strategic changes within health care institutions. Addressing these linguistic disparities is not only a matter of patient safety and quality care but also a fundamental step toward upholding Canada’s bilingual commitments in health service delivery.